The Prospect of Using Complete Feed in Goat Production: A Review on its Utility and Physical Form and Animal Responses - Simon P Ginting (Indonesian Center for Animal Research and Development, 2009)
Complete feed is a strategic feeding system that has been widely adopted by the dairy cattle industry, but it has been rarely practised in goat enterprises. The prospect of using complete feed for goat production could be considered from two aspects, namely 1) its relevancy to the goat metabolic requirement, and 2) its potential as an effective means for maximal utilization of crop residues and agro-industrial byproducts as alternative feeds. Metabolically, the higher energy requirement and the lower gut capacity of goats due to its relatively smaller body size make this animal more adapted to feedstuffs with denser nutrient contents as typified by the complete feed. As complete feed is characteristically dry, it has potential to cause hypovolemia and induce later a lower feed consumption when fed to goats. But, this event occurs only during the initial meal and the condition returns to the normal state thereafter. Total saliva secretion tend to decrease by consuming dry feed which can cause parakeratosis, laminitis or acidosis. However, these metabolic disorder could be prevented by formulating complete feed with optimal roughage/concentrate ratio. Review from literatures showed that, when used in complete feed, the inclusion rate of several low palatability crop residues or agro-industrial ranged from 15 to 60%. The roughage/concentrate ratio was in the range of 0.25 to 3.0. Some physical characteristics are important for effective complete feed such as the particle size of roughage, the content of physically effective fibre and the form of the complete feed. Complete feed processed into pellet generally resulted in better performances. The ME and CP content of complete feed used ranged from 1800 to 2800 kcal/kg DM and from 15 to 20%, respectively. The rate of feed intake by goats receiving complete feed ranged from 2.0 to 4.9% BW, the ADG ranged from 40 to 145 g, FCR ranged from 5.2 to 13.0 and DM digestibility ranged from 62 to 81%. These parameters are all influenced by the age and physiological state and the genotype of the goat as well as the physical form and the roughage/concentrate ratio of the complete feed. The carcass quality, characteristics and fatty acid compositions of goat fed complete feed are comparatively similar to those fed conventional feed. It is concluded that complete feed for goat production should be considered as an alternative and effective feeding method to maximize the utilization of local feed resources. This feeding method has huge potential for the acceleration of the development of commercial goat entrepises in the future in Indonesia. Key words: Complete feed, goats, physical characteristics, nutritive quality